Association of Abnormal Coagulation Tests in Dengue Fever with Clinical Outcomes of The Patients - Irshad, Zareen; Jaffar, Nazish; Zehra, Talat; Zeeshan, Faiza; Tashfeen, Sunila; Sheikh, Asma (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the coagulation test abnormalities (prothrombin time, activated partial thromboplastin time and fibrin degradation products) in dengue fever patients and its impact on clinical outcomes of the patient.Study Design: Cross-sectional study.Place and Duration of Study: Hematology Department, Pakistan Naval Ship Shifa Hospital, Karachi Pakistan, from Aug 2016 to Feb 2017.Methodology: A total of 135, serologically proven positive dengue-infected IgM cases, based on enzyme-linked immunesorbent assay, were included in the study. Prothrombin time, activated partial thromboplastin time, and fibrin degradation products levels were measured on STA Compact Max® (STAGO) and SysmexCA-1500. Clinical Outcomes of the patient were noted.Results: At the time of admission, elevated prothrombin time was observed in 8(5.6%) cases and remained high at the time of discharge (p-value 0.008). Elevated activated partial thromboplastin time was observed in 57 (42.2%) cases at admission whereas, at discharge, it was observed in 56 (41.5%) cases. Increased level (>5) of fibrin degradation products was seen in 30 (22.2%) cases while at the time of discharge increased level of fibrin degradation products was observed in 25 (18.5%) cases (pvalue 0.007). Out of 135 patients, mortality was observed in two cases and the remaining 133 (98.52%) survived and were discharged.Conclusion: In conclusion, prothrombin time, activated partial thromboplastin time, and fibrin degradation products can be labeled as early predictors of disease severity and their derangements are associated with clinical outcome in dengue infection.